Evaluation of the Cardiac reader® as a point-of-care instrument for measurement of fibrin D-dimers in dogs - Bauer, N.; Moritz, A. (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2009)
Objective: The aim of this study was the evaluationof the automated point-of-care analyzer Cardiac reader® for quantitative fibrin D-dimer measurement compared to the Liatest™ D-Di™ run on the bench top analyzer STA Compact (all Roche). Material and methods: 41 fresh canine blood specimens submitted from the Clinic for Small Animals, Justus-Liebig-University Giessen were included. Measurement of fibrin D-dimers with the Liatest™ D-Di™ immunoturbidimetric assay was performed in citrated blood plasma stored at –80 °C until analysis. Using the Cardiac reader, D-dimer plasma concentrations were measured with an immunological assay in heparinized fresh (< 1 hour) whole blood specimens. Results: Mean intra-assay coefficient of variation (CV) was 6.13% (range: 2.2–10.0%) for the Liatest™ D-Di and 19.8% (range: 20.1–19.6%) for the Cardiac reader. Fibrin D-dimers detected with the STA Compact exceeded the upper limit of the reference interval (0.4 μg/ml; n = 62 healthy dogs) in 20/41 samples. There was a fair correlation between D-dimer measurements with the Cardiac reader and the comparison method (r = 0.78). Generally, results were underestimated with a mean proportional bias (0.45 μg/ml). The area under the Receiver Operating Characteristic (ROC) curve was 0.895 regarding the detection of increased fibrin D-dimers with the Cardiac reader. At a cut-off value of > 0.2 μg/ml, sensitivity/specificity were 85%/91% and positive/negative likelihood ratios were 8.93/0.17. At a lower cut-off value of 0.15 μg/ml sensitivity and specificity were 90% and 66%, respectively. Conclusion and clinical relevance: The Cardiac reader can be used for quantitative measurement of canine D-dimers, however, due to the odds of false negative results and the high imprecision the comparison method should be preferred.
Keywords: Canine; disseminated intravascular coagulation; sensitivity; specificity; method validation